Response of soil heat-water processes to vegetation cover on the typical permafrost and seasonally frozen soil in the headwaters of the Yangtze and Yellow Rivers - Hu HongChang; Wang GenXu; Wang YiBo; Liu GuangSheng; Li TaiBing; Ren DongXing (Science Bulletin, 2009)
基于青藏高原江河源区典型多年冻土和季节冻土区建立的不同植被盖度下7个地温和水分观测场,对多年冻土活动层和季节冻土土壤温度和水分对植被盖度的响应分为4个阶段进行分析和对比研究.结果表明:随着植被盖度的降低,多年冻土活动层冻结深度积分减少,而季节冻土冻结深度积分增加;多年冻土冻结期负值等温线和未冻结期正值等温线的最大侵入深度和持续时间随着植被盖度降低明显增加;多年冻土活动层20～60cm的土壤含水量随着植被盖度降低而减少,而60～80cm的土壤含水量反而增加,季节冻土土壤剖面0～120cm的水分含量随着植被盖度的降低而减少.植被盖度的变化改变了冻土水热过程,且多年冻土和季节冻土对植被盖度的响应不一致. 更多 还原 The response of soil temperature and moisture to vegetative cover in the active layer of permafrost and seasonally frozen soil were assessed and compared. Soil temperature and moisture, under a range of vegetation covers (92%, 65% and 30%) in the permafrost and vegetation covers (95%, 70%-80%, 40%-50% and 10%) in the seasonally frozen soil, were measured on a daily basis. A decline in vegetation cover led to a decrease in the integral of freezing depth of active permafrost layer, but an increase in seasonally frozen soil. The maximum invasion depth and duration of the negative isotherm during the frozen period and of the positive isotherm during the non-frozen period clearly increased when vegetation cover declined. With a reduction of vegetation cover, the soil moisture in the active layer of the permafrost decreased for depths of 0.20-0.60 m, but increased for depths of 0.60-0.80 m, while for seasonally frozen soil, soil moisture of the entire profile (0.10-1.20 m) increased. Variation in vegetation cover alters soil heat-water processes, but the response to it is different between permafrost and seasonally frozen soil.